All the green year - Charlwood, D. E. 1915-2012 (Text classics, 2012)
The year I remember best from those days is 1929. This was the year I turned fourteen and went into the eigth grade;the year too that Grandfather McDonald become peculiar and we moved to live with him in his house on the cliffs